2018
DOI: 10.3126/jist.v22i2.19596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastro-Intestinal Parasites of Horse (Equus Caballus Linnaeus, 1758) In Seven Village Development Committee of Rukum District, Nepal

Abstract: This study aimed to determine the prevalence of gastro-intestinal parasites of horse in seven Village Development Committee (VDC) of Rukum district. It was carried out from March to November 2016. A total of 105 fecal samples of horses (79 males and 26 females) were collected by using opportunistic random method. The collected fecal samples were preserved in 2.5% potassium dichromate and microscopically examined using concentration techniques. The overall prevalence of gastro-intestinal parasites was 84.76% (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
6
4
0
Order By: Relevance
“…The fact that Strongylus spp. was the most prevalent parasite in our study concurs with reports from previous researchers in Nigeria (Ehizibolo et al, 2012;Umar et al, 2013;Wosu & Udobi, 2014), Pakistan (Khan et al, 2017) and Nepal (Oli & Subedi, 2018). The high prevalence of nematodes (Strongylus spp.)…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The fact that Strongylus spp. was the most prevalent parasite in our study concurs with reports from previous researchers in Nigeria (Ehizibolo et al, 2012;Umar et al, 2013;Wosu & Udobi, 2014), Pakistan (Khan et al, 2017) and Nepal (Oli & Subedi, 2018). The high prevalence of nematodes (Strongylus spp.)…”
Section: Discussionsupporting
confidence: 92%
“…Strongylus equinus is known to be the relatively least prevalent and least abundant among the other members of the genus (Taylor et al, 2016). Eimeria species has been reported to be the most important GI protozoan that affects horses within Nigeria (Useh et al, 2005;Ehizibolo et al, 2012) and outside Nigeria (Belete & Derso, 2015;Oli & Subedi, 2018). The high prevalence of multiple gastrointestinal parasites infection we recorded is expected as horses are known to harbour several species of parasites at any given time (Ehizibolo et al, 2012;Wannas et al, 2012;Umar et al, 2013;Samuel et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is higher than the study of Sapkota (2009), Matto et al (2015, and Tahir et al (2016) who reported the prevalence of 14.80%, 43.79%, and 45% in Mumbai & Pune of India, Faisalabad region of Pakistan and Lalitpur district of Nepal respectively, but lower than the Karki and Manandhar (2006) who reported the prevalence rate of 100% in Udayapur district of Nepal. Similarly, the prevalence rate in horses (81.90%) observed in the present study almost correlates with the study carried by Adeppa et al (2016) in the Shimoga region of India and Oli and Subedi (2018) in Rukum District of Nepal who reported the prevalence of 84% and 84.76% respectively, but is lower than the findings of Berhanu et al (2014) and Hasson (2014) who reported an overall prevalence of 97.9% and 100% in Hawassa Town Ethiopia and Baquba city Iraq respectively. The present findings is higher than the reports of Yadav et al (2014), Matto et al (2015, Tahir et al (2016), Ali et al (2018), and Khan et al (2020) who reported the prevalence rates of 38.69%, 38.79%, 43.33%, 44.6% and 59.25% in Faisalabad region of Pakistan, Organized farms of Mumbai and Pune, Government farm Sargodha of Pakistan, Bajaur and Mohmand agencies of Northwest Pakistan and Jabalpur of North India respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings is higher than the reports of Yadav et al (2014), Matto et al (2015, Tahir et al (2016), Ali et al (2018), and Khan et al (2020) who reported the prevalence rates of 38.69%, 38.79%, 43.33%, 44.6% and 59.25% in Faisalabad region of Pakistan, Organized farms of Mumbai and Pune, Government farm Sargodha of Pakistan, Bajaur and Mohmand agencies of Northwest Pakistan and Jabalpur of North India respectively. The variation in results regarding workers from different regions might be due to variation in the management system, geographical and climatic condition, sample size, sample collection period, and sampling method differences (Oli and Subedi 2018). The higher prevalence of gastrointestinal parasites in both horses and, mules could be due to poor feeding practice, high exposure in pasture grazing, inadequate resting time, excessive work burden and, less attention from the owners of the study area.…”
Section: Discussionmentioning
confidence: 99%